Решите уравнение 1) (2х+3)-(х-(3х+4))=5. 2) (2х-3)-(х-(3х-4))=6 3)10,4у-((4у+5)-(7-6y))=155 4)(6х+2)-(5х-4)=6

Решите уравнение 1) (2х+3)-(х-(3х+4))=5. 2) (2х-3)-(х-(3х-4))=6 3)10,4у-((4у+5)-(7-6y))=155 4)(6х+2)-(5х-4)=6
Гость
Ответ(ы) на вопрос:
Гость
2) (2х-3)-(х-(3х-4))=6 2x-3-4-x+3x-6=0 4x-13=0 4x=13 x=13/14 3) 10,4у-((4у+5)-(7-6y))=155 10.4y-4y-5+7-6y-155=0 10.4y-4y-153-6y=0 0.4y-153=0 y=153/0.4 4)(6х+2)-(5х-4)=6 6x+2+4-5x-6=0 6x-5x=0 1x=0 x=0
Не нашли ответ?
Ответить на вопрос
Похожие вопросы